(untitled) (Fiep Bulletin - online, 2013)
Integrative review of literature about the dimensions of non-remunerated traineeship in different labor scenes, nowadays world. The study had the objective of surveying in literature the boardings focused around the non-remunerated traineeship. Research developed between March and September 2008, by a survey of literature published at periodicals between 1989 and 2008, and available at databases LILACS, MEDLINE, SCIELO, BDENF, as well as documents, laws, decrees and mastering dissertations. They were found with the descriptors scholarship and traineeships, nursing and labor market. It’s evidenced that the contract of remunerated traineeships in teaching institutions means essentiality a hidden way of precarious labor in the present labor world and that students seek an internship in extra effort to complement the income of their family members besides the realization of a practice of nursing consistent with the reality of the world of work.